A systems approach to training and development - Thooyavan, K.R
This paper discusses a systematic way of conducting training, so as to achieve the goals and objectives and result in a cost effective manner. It is recommended that training should be considered necessary and important part of integrated strategy for organisational development. There is needs to be close co-ordination and involvement in the overall planning
Keywords: Systems Approach; Training